PENGARUH BENGKOANG TERHADAP PERUBAHAN SALIVA RONGGA MULUT - Ulliana Ulliana; Shinta Wijayanti S; Baby Prabowo Setyawati; Winarno Winarno (Poltekkes Kemenkes Bandung, 2022)
Saliva is a complex fluid in maintaining healthy teeth and mouth. One of the ingredients based on local wisdom that can be used as a natural cleanser from plaque and debris on teeth is Jicama. Jicama has a very large content of water and fiber, Chewing Jicama can stimulate and increase salivation. This study aims to determine the effect of Jicama on changes saliva in the oral cavity.The type of research used is Quasi-Experimental using pre and post design with non control group design. The population of this study is all level II students of AKG Puskesad. The total sampling was 36 respondents. Data analysis using the Wilcoxon and Kruskal Wallis Tests.The results of the results of the analysis test of this study showed that the average pH value of saliva before and after chewing Jicama decreased with a value of 18.90 to 16.50 (p-value = 0.001), a saliva viscosity value of 18.00 to 0.00 (p-value = 0.001) and a buffer capacity value increased from a value of 12.00 to 12.55 (p-value = 0.001). The correlation test between saliva Ph and saliva viscosity obtained a value of r = 0.526 (p-value = 0.001). The Effect of Jicama on Changes in pH, Viscosity and Saliva buffer capacity.